A silicon-carbon composite negative electrode material, and its preparation method and application
Through the heat treatment of silicon magnesium alloy materials and dopants and humic acid coating technology, graphene-coated silicon-carbon composite anode material is generated, which solves the problem of low capacity retention of silicon-carbon anode materials in the prior art, and achieves high energy density and good cycle stability and rate performance.
Patent Information
- Application Number
- CN202411488419.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing silicon-carbon anode material with high porosity and low volume expansion has a capacity retention rate of less than 40% in lithium-ion batteries, which cannot meet the needs of high energy density and high power density.
The silicon magnesium alloy material is mixed with the dopant and CO2 gas is used for heating, cooling and etching, and then humic acid is added to coat and calcined to form graphene-coated heteroatom doped @ low carbon deposition porous silicon material.
The capacity retention rate, cycle stability and rate performance of the battery are improved, while improving silicon volume expansion and preparation of high-capacity negative electrode materials are achieved.
Smart Images

Figure CN119008920B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite negative electrode material, and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic products in the past decade, the pursuit of high energy and high power density lithium-ion batteries at a reasonable cost constitutes a potential research field, which supports important applications from portable electronic products to electric vehicles and large-scale stationary energy storage. High-capacity anode materials are an important component of the next generation of high energy density lithium-ion batteries, which are mainly divided into metal anodes (such as Li) and silicon-based anodes. However, silicon causes electrode pulverization due to its volume expansion changes during charging and discharging, and cannot produce a stable SEI film. The continuous consumption of lithium causes a large amount of irreversible capacity loss and accelerates capacity decay; secondly, silicon has poor conductivity and diffusivity, resulting in low first coulomb efficiency and poor rate performance. Therefore, it is urgent to improve the defects of silicon volume expansion and low conductivity. Researchers have constructed silicon anode structures from one-dimensional to three-dimensional, mainly including alloys with metals and non-metals or simple composites, which can achieve the effect of improving its defects to a certain extent.
[0003] China's CN118117081A patent introduces a method for preparing a silicon-carbon negative electrode material with high porosity and low volume expansion. First, magnesium silicate lithium sol is added to a calcium chloride silicon powder aqueous solution, which is beneficial to the Ca in calcium chloride. 2+ Adsorbed on the surface of nano-lithium magnesium silicate, at the same time, nano-scale lithium magnesium silicate is conducive to loading on the surface of silicon, helping to fully deposit on the surface of silicon. After etching, the porosity of the silicon surface is increased; at the same time, because lithium magnesium silicate is loaded on the surface of silicon, it also helps to reduce the volume expansion of silicon during the charging and discharging process, and improve the cycle stability of the negative electrode material during the charging and discharging process. The presence of the lithium magnesium silicate film in this technology can isolate the core silicon from the electrolyte, reduce the occurrence of side reactions on the silicon surface, and help improve the rate performance of the battery. However, at a current density of 1A / g, the capacity retention rate is less than 40%, indicating that this technology still needs to be improved. Summary of the invention
[0004] In order to overcome the problem of low capacity retention rate of batteries prepared with silicon-carbon negative electrode materials with high porosity and low volume expansion in the prior art, the present invention provides a silicon-carbon composite negative electrode material preparation and application thereof. The preparation method is simple and efficient, and the battery prepared with the obtained negative electrode material has high capacity and good rate performance.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The present invention provides a silicon-carbon composite negative electrode material, which contains 60%-70% silicon, 20%-30% carbon, 5%-8% oxygen, 0.1%-1% sulfur, 0.1%-1% boron and 0.01%-0.5% phosphorus; the percentage is the percentage of each element in the total mass of the silicon-carbon composite negative electrode material;
[0007] The silicon-carbon composite negative electrode material is a three-layer coated chestnut-shaped structure, the core is heteroatom-doped porous silicon, the first layer is a silicon oxide layer; the second layer is a carbon layer; and the third layer is a graphene layer.
[0008] In a preferred embodiment, the silicon-carbon composite negative electrode material contains 61.8%-68.1% silicon.
[0009] In a preferred embodiment, the silicon-carbon composite negative electrode material contains 21.93%-29.24% of carbon element.
[0010] In a preferred embodiment, the silicon-carbon composite negative electrode material contains 5.87%-7.01% oxygen.
[0011] In a preferred embodiment, the silicon-carbon composite negative electrode material contains 0.58%-0.81% sulfur.
[0012] In a preferred embodiment, the silicon-carbon composite negative electrode material contains 0.43%-0.63% of boron.
[0013] In a preferred embodiment, the silicon-carbon composite negative electrode material contains 0.09%-0.27% phosphorus.
[0014] In a preferred embodiment, the D50 of the silicon-carbon composite negative electrode material is 130-165nm; preferably 135-160nm, such as 150nm, 145nm, 155nm, 160nm, 135nm and 140nm.
[0015] In a preferred embodiment, the electrical conductivity of the silicon-carbon composite negative electrode material is 8×10^3-10×10^3S / m, preferably 8.199×10^3-9.975×10^3S / m, for example, 8.946×10^3S / m, 9.108×10^3S / m, 8.995×10^3S / m, 9.412×10^3S / m, 8.309×10^3S / m, 9.975×10^3S / m, 9.878×10^3S / m, 9.889×10^3S / m, 9.297×10^3S / m, 8.199×10^3S / m or 8.678×10^3S / m; the electrical conductivity adopts the model OrionStar TMA212 conductivity benchtop meter measured at room temperature.
[0016] In a preferred embodiment, the pore size of the silicon-carbon composite negative electrode material is 14-18 nm, preferably 14.9-17.8 nm, for example, 16.7 nm, 14.9 nm, 17.8 nm, 15.7 nm, 16.2 nm, 17.1 nm, 17.2 nm, 14.9 nm, 15.1 nm, 16.8 nm or 18.2 nm.
[0017] In a preferred embodiment, the charge transfer internal resistance of the silicon-carbon composite negative electrode material is 27-37Ω, preferably 27.4-36.8Ω, for example, 32.5Ω, 29.8Ω, 34.2Ω, 27.4Ω, 31.7Ω, 34.8Ω, 36.8Ω, 32.9Ω, 29.5Ω, 28.4Ω or 35.1Ω, and the transfer internal resistance is measured by electrochemical impedance spectroscopy (compacted density 1.65g / cm 3 ) measured.
[0018] In a preferred embodiment, the first coulombic efficiency of the silicon-carbon composite negative electrode material is 93-95%, preferably 93.2-94.9%.
[0019] The present invention provides a method for preparing the silicon-carbon composite negative electrode material as described above, which comprises the following steps:
[0020] (1) Silicon magnesium alloy material (Mg2Si) and dopant are mixed and then heated by introducing CO2 gas. After cooling, hydrochloric acid is added for etching, and then washed, filtered and dried to obtain heteroatom-doped low-carbon deposited porous silicon material.
[0021] (2) After mixing the heteroatom-doped @low carbon deposition porous silicon material, humic acid and deionized water, adding ammonia water to obtain a mixed solution, removing the solvent in the mixed solution to obtain the humic acid-coated heteroatom-doped @low carbon deposition porous silicon material, and calcining the humic acid-coated heteroatom-doped @low carbon deposition porous silicon material to obtain the graphene-coated heteroatom-doped @low carbon deposition porous silicon material.
[0022] In a preferred embodiment, in step (1), the silicon-magnesium alloy material is commercially available or prepared by the following method, wherein the method comprises the following steps:
[0023] The silicon source and magnesium powder are mixed and ground to obtain a silicon-magnesium alloy precursor, and the silicon-magnesium alloy precursor is subjected to a hot-melt treatment to obtain a silicon-magnesium alloy material under an inert atmosphere.
[0024] In a preferred embodiment, in the method for preparing the silicon-magnesium alloy material, the silicon source is silicon powder, silicon dioxide powder or silicon oxide powder, preferably silicon powder or silicon dioxide powder; the D50 of the silicon source is 50-100nm, for example 70nm.
[0025] In a preferred embodiment, in the method for preparing the silicon-magnesium alloy material, the D50 of the magnesium powder is 50-100 μm, for example, 75 μm.
[0026] In a preferred embodiment, in the method for preparing the silicon-magnesium alloy material, the mass ratio of the silicon source to the magnesium powder is 1:(1.5-6), preferably 1:(1.5-3), for example 1:2.
[0027] In a preferred embodiment, in the preparation method of silicon-magnesium alloy material, the grinding method is ball milling in a ball mill, and the ball-to-material ratio of the ball mill can be (30-60):1, for example, 50:1; the rotation speed of the ball mill can be 550-750r / min, for example, 600r / min, and the ball milling time can be 4-10h, for example, 6h.
[0028] In a preferred embodiment, in the method for preparing the silicon-magnesium alloy material, the temperature of the hot melt is 600-900°C, such as 650-700°C.
[0029] In a preferred embodiment, in the method for preparing the silicon-magnesium alloy material, the hot melting time is 3-10 hours, for example, 6 hours.
[0030] In a preferred embodiment, in the method for preparing the silicon-magnesium alloy material, the heating rate of the hot melt is 1-10° C. / min.
[0031] In the present invention, the inert atmosphere is a conventional inert atmosphere in the art; in a preferred embodiment, in the method for preparing the silicon-magnesium alloy material, the inert atmosphere is argon, helium, neon or nitrogen.
[0032] In a preferred embodiment, in step (1), the dopant is a mixture of boron trioxide, phosphorus pentoxide and sulfur trioxide; the mass ratio of boron trioxide, phosphorus pentoxide and sulfur trioxide can be (1-2.5): (0.5-1): (2-3.5); for example, 1.5: (0.8-1): 2.3.
[0033] In a preferred embodiment, in step (1), the mass ratio of the silicon-magnesium alloy material to the dopant is 1:(5-20), preferably 1:(5-10), such as 1:7.5 or 1:10.
[0034] In a preferred embodiment, in step (1), the flow rate of the CO2 gas is 60-100 mL / min, for example 80 mL / min.
[0035] In a preferred embodiment, in step (1), the heating rate is 3-15°C / min, for example, 5-10°C / min.
[0036] In a preferred embodiment, in step (1), the heating temperature is 650-900°C, such as 700-750°C.
[0037] In a preferred embodiment, in step (1), the heating time is 24-48 hours, for example 28 hours.
[0038] In a preferred embodiment, in step (1), the cooling temperature is room temperature.
[0039] In a preferred embodiment, in step (1), the mass fraction of the hydrochloric acid is 6%-10%, for example 8%.
[0040] In a preferred embodiment, in step (1), the etching time is 12-18 hours, for example, 14 hours.
[0041] In a preferred embodiment, in step (1), the pH of the water wash is neutral.
[0042] In a preferred embodiment, in step (1), the drying method is freeze drying, CO2 supercritical drying or vacuum drying; the freeze drying temperature can be -30°C to -80°C, and the freeze drying time can be 3-7h; the CO2 supercritical drying temperature can be 10-40°C, the CO2 supercritical drying pressure can be 10-15kPa, and the CO2 supercritical drying time can be 1-3h; the vacuum drying temperature can be 80-100°C, and the vacuum drying time can be 6-24h.
[0043] In a preferred embodiment, in step (2), the mass ratio of heteroatom-doped low-carbon deposited porous silicon material to humic acid is (4.25-9.5):1, preferably (6-9):1, and further preferably 6:1.5, 8.5:1 or 9:1.
[0044] In a preferred embodiment, in step (2), the mass ratio of the liquid (water) to the solid (heteroatom-doped @low-carbon deposited porous silicon material and humic acid) is (10-15):1, for example 10:1.
[0045] In a preferred embodiment, in step (2), the concentration of the aqueous ammonia is 26-30 wt%, for example 28 wt%.
[0046] In a preferred embodiment, in step (2), the method of removing the solvent from the mixed solution is to heat and evaporate the solvent at a constant temperature, and the heating temperature is 80-100°C, for example 85°C.
[0047] In a preferred embodiment, in step (2), the calcination is divided into two stages, the temperature of the first stage calcination is 200-300°C, for example, 200-280°C; the time of the first stage calcination is 1-3h, for example, 2h; the temperature of the second stage calcination is 500-850°C, for example, 600-650°C; the heating rate of the second stage calcination is 1-10°C / min, for example, 3°C / min; the time of the second stage calcination is 8-15h, for example, 10h; the second stage calcination can be carried out under an inert atmosphere;
[0048] Furthermore, cooling may be performed between the two stages of calcination.
[0049] The present invention also provides a graphene-coated heteroatom-doped low-carbon deposited porous silicon material, which is prepared by the above-mentioned preparation method.
[0050] The present invention also provides a use of the above-mentioned graphene-coated heteroatom-doped low-carbon deposited porous silicon material in the preparation of a negative electrode material for a battery.
[0051] Definition of terms
[0052] In the present invention, "room temperature" refers to "10 to 40°C".
[0053] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0054] The reagents and raw materials used in the present invention are commercially available.
[0055] The positive and progressive effects of the present invention are as follows: the preparation method of the present invention utilizes the strong reducing properties of silicon-magnesium alloy and uses CO2 gas as a carbon source to prepare a doped silicon-carbon composite material, thereby achieving improvement in silicon volume expansion and obtaining a high-capacity negative electrode material while also achieving the recycling of greenhouse gases; further utilizing humic acid to coat the in-situ generated graphene to further protect its silicon-carbon structure, so that the battery prepared thereby has a high capacity while also obtaining good cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 A schematic diagram of the structure of a composite negative electrode material prepared by the method of Example 1 of the present invention;
[0057] Figure 2 A schematic diagram of the cycle performance of a composite negative electrode material prepared by the method of Example 1 of the present invention;
[0058] Figure 3 Schematic diagram of the rate performance of a composite negative electrode material prepared by the method of Example 1 of the present invention. DETAILED DESCRIPTION
[0059] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0060] Example 1
[0061] (1) Silicon powder (D50 = 70nm) and magnesium powder (D50 = 75μm) were fed into a ball mill at a mass ratio of 1.5:4, with a ball-to-material ratio of 50:1, a ball milling speed of 600r / min, and a ball milling time of 6h to obtain a silicon-magnesium alloy precursor. Then 6g of the silicon-magnesium alloy precursor was fed into a temperature-controlled tubular furnace, heated from room temperature to 650℃, with a heating rate of 1-10℃ / min, and heat-melted at 650℃ for 6h under an inert atmosphere (argon) to obtain a silicon-magnesium alloy material.
[0062] (2) The obtained silicon-magnesium alloy material was mixed with dopants (boron trioxide / phosphorus pentoxide / sulfur trioxide mass ratio of 1.5:0.8:2.3) at a mass ratio of 1.5:15, and sent into a tube furnace, the gas was CO2 (flow rate 80mL / min), the heating rate was 5℃ / min, after heating to 700℃, heat treated at 700℃ for 28h, and then cooled to room temperature. The obtained product was etched with 8% hydrochloric acid for 14h, repeatedly rinsed with distilled water until the pH was neutral, filtered, and dried to obtain heteroatom-doped @ low-carbon deposited porous silicon material.
[0063] (3) Adding heteroatom-doped @low-carbon-deposited porous silicon material and humic acid powder in a mass ratio of 90:10 to deionized water and mixing evenly, controlling the solid-liquid ratio at 1:10, then adding ammonia solution with a concentration of 28wt% under stirring conditions until the humic acid powder is completely dissolved, then heating to 85°C and evaporating the solvent at a constant temperature to uniformly coat the humic acid on the surface of the heteroatom-doped @low-carbon-deposited porous silicon material to obtain humic acid-coated heteroatom-doped @low-carbon-deposited porous silicon material; placing the humic acid-coated heteroatom-doped @low-carbon-deposited porous silicon material in a microwave oven at 200°C for 2h, cooling and taking it out, then placing it in a tubular furnace in an inert atmosphere, heating it to 600°C at a rate of 3°C / min, and heating it at 600°C for 10h, so that the humic acid is thermally decomposed and graphene is synthesized in situ to obtain graphene-coated heteroatom-doped @low-carbon-deposited porous silicon material. The structural schematic diagram is shown in FIG. Figure 1 shown.
[0064] Example 2
[0065] The difference from Example 1 is that in step (1), the mass ratio of silicon powder to magnesium powder is 1.5:3.
[0066] Example 3
[0067] The difference from Example 1 is that the heat treatment temperature in step (1) is 700°C.
[0068] Example 4
[0069] The difference from Example 1 is that in step (1), the silicon powder is replaced by silicon dioxide powder.
[0070] Example 5
[0071] The difference from Example 1 lies in the dopant in step (2) (boron trioxide / phosphorus pentoxide / sulfur trioxide ratio is 1.5:1:2.3).
[0072] Example 6
[0073] The difference from Example 1 is that the heating rate in step (2) is 10°C / min.
[0074] Example 7
[0075] The difference from Example 1 is that the heat treatment temperature in step (2) is 750°C.
[0076] Example 8
[0077] The difference from Example 1 is that in step (2), the mass ratio of the silicon-magnesium alloy material to the dopant is 2:15.
[0078] Example 9
[0079] The difference from Example 1 is that in step (3), the mass ratio of the heteroatom-doped low-carbon deposited porous silicon material and the humic acid powder is 90:15.
[0080] Example 10
[0081] The difference from Example 1 is that the first heat treatment temperature in step (3) is 280°C.
[0082] Embodiment 11
[0083] The difference from Example 1 is that the secondary heat treatment temperature in step (3) is 650°C.
[0084] Comparative Example 1:
[0085] The difference from Example 1 is that the raw material of step (1) is pure silicon powder and does not contain magnesium powder.
[0086] Comparative Example 2:
[0087] The difference from Example 1 is that there are only steps (1) and (2).
[0088] Comparative Example 3:
[0089] The difference from Example 1 is that there is only step (1).
[0090] Physical and chemical properties test:
[0091] After XRF testing, the element content in the composite material synthesized by the present invention was tested by microwave digestion method. The example was pre-treated by mixing 2±0.05g of stearic acid and 6±0.5g of the sample to be tested, grinding them, pressing them into tablets, and then testing them in Avio™ 200 equipment; the test conditions were: the air pressure was greater than 2MPa. The conductivity was measured by Orion Star TM The conductivity was measured by A212 benchtop meter at room temperature. The pore size was measured by POROLUX Cito instrument; the internal resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 )The above physical and chemical results are described in the following table.
[0092] Table 1:
[0093]
[0094]
[0095] Lithium-ion button cell battery testing:
[0096] The preparation method of the button cell used for testing the electrochemical performance is as follows: the battery negative electrode material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), CMC, and SBR according to 95.5:1.5:1.5:1.5, and applied on the copper foil. The compaction density is 1.60g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte uses a mixture of 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is a PE / PP / PE composite film, and assembled into a button battery. The test conditions are: rate charge and discharge at a current density of 0.1A / g-2A / g, and the charging voltage is limited to 0.005-2V. The test results of Example 1 at a rate of 0.1Ah / g current density (within 50 cycles) are as follows Figure 3 As shown, the test results of Example 1 at a current density of 0.1Ah / g and the cycle performance (within 200 cycles) are as follows Figure 2 shown.
[0097] Table 2:
[0098]
[0099] 。
Claims
1. A silicon-carbon composite negative electrode material, characterized in that: It contains 60%-70% silicon, 20%-30% carbon, 5%-8% oxygen, 0.58%-0.81% sulfur, 0.43%-0.63% boron and 0.01%-0.27% phosphorus; the percentage is the percentage of each element in the total mass of the silicon-carbon composite negative electrode material; The silicon-carbon composite negative electrode material is a three-layer coated chestnut-shaped structure, the core is heteroatom-doped porous silicon, the first layer is a silicon oxide layer; the second layer is a carbon layer; and the third layer is a graphene layer; The heteroatom doped with the heteroatom is sulfur, boron and phosphorus.
2. The silicon-carbon composite negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The silicon-carbon composite negative electrode material contains 61.8%-68.1% silicon; (2) The silicon-carbon composite negative electrode material contains 21.93%-29.24% carbon element; (3) The silicon-carbon composite negative electrode material contains 5.87%-7.01% oxygen; (4) The D50 of the silicon-carbon composite negative electrode material is 130-165nm; (5) The electrical conductivity of the silicon-carbon composite negative electrode material is 8×10^3-10×10^3S / m; (6) The pore size of the silicon-carbon composite negative electrode material is 14-18 nm; (7) The charge transfer internal resistance of the silicon-carbon composite negative electrode material is 27-37Ω; (8) The first coulombic efficiency of the silicon-carbon composite negative electrode material is 93-95%; The silicon-carbon composite negative electrode material described in (9) contains 0.09%-0.27% phosphorus.
3. The silicon-carbon composite negative electrode material according to claim 2, characterized in that: It meets one or more of the following conditions: (1) The D50 of the silicon-carbon composite negative electrode material is 135-160nm; (2) The electrical conductivity of the silicon-carbon composite negative electrode material is 8.199×10^3-9.975×10^3S / m; (3) The pore size of the silicon-carbon composite negative electrode material is 14.9-17.8 nm; (4) The charge transfer internal resistance of the silicon-carbon composite negative electrode material is 27.4-36.8Ω; The first coulombic efficiency of the silicon-carbon composite negative electrode material described in (5) is 93.2-94.9%.
4. The silicon-carbon composite negative electrode material according to claim 3, characterized in that: It meets one or more of the following conditions: (1) The D50 of the silicon-carbon composite negative electrode material is 150nm, 145nm, 155nm, 160nm, 135nm or 140nm; (2) The electrical conductivity of the silicon-carbon composite negative electrode material is 8.946×10^3S / m, 9.108×10^3S / m, 8.995×10^3S / m, 9.412×10^3S / m, 8.309×10^3S / m, 9.975×10^3S / m, 9.878×10^3S / m, 9.889×10^3S / m, 9.297×10^3S / m, 8.199×10^3S / m or 8.678×10^3S / m; (3) The pore size of the silicon-carbon composite negative electrode material is 16.7 nm, 14.9 nm, 17.8 nm, 15.7 nm, 16.2 nm, 17.1 nm, 17.2 nm, 15.1 nm, 16.8 nm or 18.2 nm; The charge transfer internal resistance of the silicon-carbon composite negative electrode material described in (4) is 32.5Ω, 29.8Ω, 34.2Ω, 27.4Ω, 31.7Ω, 34.8Ω, 36.8Ω, 32.9Ω, 29.5Ω, 28.4Ω or 35.1Ω.
5. A method for preparing a silicon-carbon composite negative electrode material as claimed in claim 1, characterized in that: It includes the following steps: (1) After mixing silicon-magnesium alloy material and dopant, CO2 gas is introduced to heat the mixture, cooled, etched with hydrochloric acid, washed with water, filtered and dried to obtain heteroatom-doped low-carbon deposited porous silicon material; In step (1), the dopant is a mixture of boron trioxide, phosphorus pentoxide and sulfur trioxide; the mass ratio of the boron trioxide, the mass of the phosphorus pentoxide and the mass of the sulfur trioxide is (1-2.5):(0.5-1):(2-3.5); the mass ratio of the silicon-magnesium alloy material to the dopant is 1:(5-20); (2) After mixing the heteroatom-doped @low carbon deposition porous silicon material, humic acid and deionized water, adding ammonia water to obtain a mixed solution, removing the solvent in the mixed solution to obtain the humic acid-coated heteroatom-doped @low carbon deposition porous silicon material, and calcining the humic acid-coated heteroatom-doped @low carbon deposition porous silicon material to obtain the graphene-coated heteroatom-doped @low carbon deposition porous silicon material.
6. The method for preparing the silicon-carbon composite negative electrode material according to claim 5, characterized in that: In step (1), the silicon-magnesium alloy material is prepared by the following method: The method comprises the following steps: mixing and grinding silicon source and magnesium powder to obtain silicon-magnesium alloy precursor, and subjecting the silicon-magnesium alloy precursor to hot-melt treatment to obtain silicon-magnesium alloy material under an inert atmosphere.
7. The method for preparing the silicon-carbon composite negative electrode material according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The silicon source is silicon powder, silicon dioxide powder or silicon monoxide powder; the D50 of the silicon source is 50-100nm; (2) The D50 of the magnesium powder is 50-100 μm; (3) The mass ratio of the silicon source to the magnesium powder is 1:(1.5-6); (4) The grinding method is ball milling in a ball mill, the ball-to-material ratio of the ball mill is (30-60):1; the rotation speed of the ball mill is 550-750 r / min, and the ball milling time is 4-10 h; (5) The temperature of the hot melt is 600-900°C; (6) The hot melting time is 3-10 hours; (7) The heating rate of the hot melt is 1-10°C / min; and (8) the inert atmosphere is argon, helium, neon or nitrogen.
8. The method for preparing the silicon-carbon composite negative electrode material according to claim 7, characterized in that: It meets one or more of the following conditions: (1) The silicon source is silicon powder or silicon dioxide powder; the D50 of the silicon source is 70 nm; (2) The D50 of the magnesium powder is 75 μm; (3) The mass ratio of the silicon source to the magnesium powder is 1:(1.5-3); (4) The grinding method is ball milling in a ball mill, the ball-to-material ratio of the ball mill is 50:1; the rotation speed of the ball mill is 600 r / min, and the ball milling time is 6 hours; (5) The hot melt temperature is 650-700°C; And the hot melting time described in (6) is 6 hours.
9. The method for preparing the silicon-carbon composite negative electrode material according to claim 8, characterized in that: The mass ratio of the silicon source to the magnesium powder is 1:
2.
10. The method for preparing the silicon-carbon composite negative electrode material according to claim 5, characterized in that: It meets one or more of the following conditions: (1) In step (1), the flow rate of the CO2 gas is 60-100 mL / min; (2) In step (1), the heating rate is 3-15°C / min; (3) In step (1), the heating temperature is 650-900°C; (4) In step (1), the heating time is 24-48 hours; (5) In step (1), the cooling temperature is room temperature; (6) In step (1), the mass fraction of the hydrochloric acid is 6%-10%; (7) In step (1), the etching time is 12-18 hours; (8) In step (1), the pH of the water wash is neutral; (9) In step (1), the drying method is freeze drying, CO2 supercritical drying or vacuum drying; (10) In step (2), the mass ratio of the heteroatom-doped@low-carbon deposited porous silicon material to the mass ratio of the humic acid is (4.25-9.5): 1; (11) In step (2), the mass ratio of the deionized water to the mass ratio of the heteroatom-doped @low-carbon deposited porous silicon material and the humic acid is (10-15): 1; (12) In step (2), the concentration of the aqueous ammonia is 26-30 wt%; (13) In step (2), the method of removing the solvent from the mixed solution is to heat and evaporate the solvent at a constant temperature, and the heating temperature is 80-100°C; and (14) in step (2), the calcination is divided into two stages, the calcination temperature of the first stage is 200-300°C; the calcination time of the first stage is 1-3h; the calcination temperature of the second stage is 500-850°C; the heating rate of the second stage calcination is 1-10°C / min; and the calcination time of the second stage is 8-15h.
11. The method for preparing a silicon-carbon composite negative electrode material according to claim 10, characterized in that: It meets one or more of the following conditions: (1) In step (1), the mass ratio of the silicon-magnesium alloy material to the dopant is 1:(5-10); (2) In step (1), the flow rate of the CO2 gas is 80 mL / min; (3) In step (1), the heating rate is 5-10°C / min; (4) In step (1), the heating temperature is 700-750°C; (5) In step (1), the heating time is 28 hours; (6) In step (1), the mass fraction of hydrochloric acid is 8%; (7) In step (1), the etching time is 14 h; (8) In step (1), the freeze drying temperature is -30°C to -80°C, and the freeze drying time is 3-7h; the CO2 supercritical drying temperature is 10-40°C, the CO2 supercritical drying pressure is 10-15kPa, and the CO2 supercritical drying time is 1-3h; the vacuum drying temperature is 80-100°C, and the vacuum drying time is 6-24h; (9) In step (2), the mass ratio of the heteroatom-doped@low-carbon deposited porous silicon material to the mass ratio of the humic acid is (6-9): 1; (10) In step (2), the mass ratio of the deionized water to the heteroatom-doped low-carbon deposited porous silicon material and humic acid is 10:1; (11) In step (2), the concentration of the aqueous ammonia is 28 wt %; and (12) in step (2), the calcination is divided into two stages, the calcination temperature of the first stage is 200-280°C; the calcination time of the first stage is 2h; the calcination temperature of the second stage is 600-650°C; the heating rate of the second stage calcination is 3°C / min; the calcination time of the second stage is 10h; the calcination of the second stage is carried out under an inert atmosphere.
12. The method for preparing a silicon-carbon composite negative electrode material according to claim 11, characterized in that: It meets one or more of the following conditions: (1) In step (1), the mass ratio of the boron trioxide, the phosphorus pentoxide and the sulfur trioxide is 1.5:(0.8-1):2.3; (2) In step (1), the mass ratio of the silicon-magnesium alloy material to the dopant is 1:7.5 or 1:10; (3) In step (2), the mass ratio of the heteroatom-doped @low-carbon deposited porous silicon material to the humic acid is 6:1.5, 8.5:1 or 9:1; (4) In step (2), the method of removing the solvent from the mixed solution is to heat and evaporate the solvent at a constant temperature, and the heating temperature is 85°C; and (5) in step (2), cooling is performed between the two stages of calcination.
13. A graphene-coated heteroatom-doped low-carbon deposited porous silicon material, characterized in that: It is prepared by the preparation method described in any one of claims 5 to 12.
14. Use of the graphene-coated heteroatom-doped low-carbon deposited porous silicon material as claimed in claim 13 in preparing anode materials for batteries.
Citation Information
Patent Citations
Preparation method of silicon-carbon negative electrode material with high porosity and low volume expansion
CN118117081A
Sheet-shaped boron-doped porous silicon electrode material and preparation method thereof
CN108390053A
Spherical nano porous silicon / silicon oxide / carbon composite material for lithium ion battery and preparation method thereof
CN110335993A
Silicon-carbon composite material with double-layer carbon coating structure and preparation method and application thereof
CN111342010A
Silicon-carbon negative electrode material and preparation method and application thereof
CN116825984A